APLIKASI STRUKTUR HIBRIDA RANGKA RUANG, MEMBRAN DAN KABEL PADA ARENA BALAP SEPEDA VELODROME - Zulwindra, Yudha; Muktiono, Ayub (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2022)
In building a building, we must know what type of structure is right for use, wide-span structural systems are ofseveral kinds, such as cable structure systems, arc structure systems, dome structure systems, shell structuralsystems, pneumatic structural systems, membrane structure systems, systems space frame structure and foldplane structure system. Therefore we have to adjust the shape of the structure to the building we are going tobuild. For example, when we are going to build a mosque, we have to use a structural system in accordance withthe mosque building, if we are wrong to apply the structure to the building we are going to make, the buildingwill lose its aesthetic and architectural value. So it is very important for us to understand the various types andfunctions of the structural system itself. Before that we need to understand that a wide-span building is a buildingthat allows the use of column-free space as wide and as long as possible. Wide-span buildings are usually used toaccommodate activities that require a large enough column-free space, such as for sports activities in the form ofa stadium building, a performance hall, an auditorium, and exhibition activities or exhibition buildings. If thebuilding has a span of less than 10 meters, then we don't have to use the structural system to save constructioncosts, we can just use the general structural system.